PENGARUH MEDIA POWTOON DALAM PEMBELAJARAN TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMPN 1 KREMBUNG - Kiki Yuni Murtiyastuti (Journal of Education and Learning Sciences, 2022)
The purpose of this study was to show the effect of Powtoon media on the learning of text based on the observations of class VII students of SMPN 1 Krembung. This study uses a quantitative approach with the type of experiment one group pretest posttest design. The subjects of this study were students of class VII-5 SMPN 1 Krembung in the academic year 2021/2022. The research sample was determined by purposive sampling technique. The instruments used are questionnaires and test questions. The data in this study were the results of the questionnaire and the pretest posttest scores. Testing the validity and reliability of the instrument as well as data processing using the SPSS 16.0 for windows program. The results showed that testing the hypothesis using the paired sample t-test t-test obtained results tcount = -6854, while ttable with df N-1 = 30 and a significance level of 5% (0.05) of 2.042. So, tcount > ttable (-6.854 > 2.042) with Sig. (2 tailed) 0.000 < 0.05 then Ha is accepted and H0 is rejected. This is reinforced by the results of student responses to the use of Powtoon media by 81%. The percentage is categorized as good. Thus, this Powtoon media can be said to be influential and effective in learning the observational report text in class VII SMPN 1 Krembung for the 2021/2022 academic year